Stability indicating RP-HPLC method for estimation of finerenone and its related substances in new dosage form - Aya A. Marie; Mohamed G. Yassin; Eman A. Elshenawy (Scientific Reports)
Abstract Stability indicating RP-HPLC method was developed and validated for the estimation of finerenone (FIN) in pure and in new tablet dosage form. The proposed approach was applied and validated for determination of (FIN) related substances. Stability studies of (FIN) was carried out using five stress conditions; acid, alkali, oxidation, photodegradation and heat degradation. The chromatographic analysis of (FIN) was based on using mobile phase consist of filtered and degassed mixture of 450mL water, 550mL acetonitrile and 10mL triethylamine with pH adjusted to 7. Phenomenex (C18, 4.6 × 250 mm, 5 μm) column was used with 0.8 mL/min flow rate and 40 °C column temperature. The UV detection was set at 252 nm with injection volume (10µL). The (FIN) retention time was 4.437 ± 0.05 min. The proposed technique was validated according to ICH guidelines with good linearity in ranges (8–30 µg/mL) for assay of (FIN) and (0.2–1.4 µg/mL) for determination of (FIN) unspecified impurities. The found mean percentage recoveries were 99.74% for (FIN) assay and 99.11% for (FIN) related substance determination which indicate good trueness. The developed approach was successfully applied for the determination of (FIN) in Nexifinerenone® film coated tablet dosage form. Good agreement was established when assay results using the validated RP-HPLC method were compared statistically to those obtained using the reported method. For the greenness assessment Complex GAPI, Complex MoGAPI and AGREE methods were applied.